Food and Food Waste in the Qur’ān: A Thematic Approach - Lamuwala, Ali Asghar; Siddiqui, Umair Mahmood (Islamic Studies, 2025)
Food waste is a pressing global issue with profound environmental, economic, and social consequences. The Qur’ān, which reveres food as a divine blessing, provides ethical and practical insights into addressing this challenge. This paper thematically examines the Qur’ānic view of food as a necessity of human beings and its provision by Allah. It also explores Qur’ānic guidance on food waste mitigation by identifying its drivers and proposing solutions rooted in the scripture. For instance, the abundance of food and overproduction have been identified as drivers of food waste by the Qur’ān. Other contributors include spoilage due to natural and anthropogenic factors, such as negligence in resource management. Moreover, the study examines Qur’ānic solutions for mitigation, emphasizing the role of moderate and mindful consumption, source reduction, charity, repurposing, and composting. Mindful consumption has also been promoted through many of the Qur’ānic injunctions and relevant strategies, such as preparing food by one’s own hands to foster a deeper appreciation for sustenance, thereby mitigating waste. The analysis of tafsīr literature reveals specific instances where sufficiency of food has been prioritized over excess, promoting sustainable food choices. Previous research has dealt with the Islamic perspectives of food waste, but a thorough study, especially based on scriptural insights, remains underexplored. This study addresses this gap by thematically examining the Qur’ānic verses that highlight a profound concern for food waste mitigation. The findings hold particular relevance for Muslim societies grappling with excessive food waste, emphasizing the growing importance of religious approaches in addressing this critical issue, especially in Muslim societies.